Optimalisasi Pengelolaan Lahan Parkir Menggunakan Program Integer Metode Branch And Bound Di Mall Plaza Medan Fair - Mestria Cicilia Panjaitan; Abil Mansyur (Pusat riset dan Inovasi Nasional, 2023)
The rapid development of vehicles has an impact on increasing the need for parking space, thus demanding the need for availability and land management that provides convenience and comfort for motorists. Plaza Medan Fair mall is still not optimal in planning and managing parking lots, this can be seen from the number of vehicles that do not get parking spaces while parking is still available, besides that the placement of parking cars has not been arranged so that visitors still have difficulty in finding a parking space. This can have an impact on not optimal parking lot income. Parking lot management can be done by classifying parking by categorizing vehicles according to their group considering that each vehicle has a different size and can be grouped according to type. Optimization of parking management can be done using the branch and bound method integer program. The branch and bound method is a method to find the optimal solution to the integer problem with the concept of branching and bounding. The results of the study found that there were 200 parking spaces for small cars, 651 parking spaces, 651 parking spaces, 226 large cars and 70 parking spaces. The maximum parking income obtained by Plaza Medan Fair mall is Rp10,023,000.-.